LISTENING STRATEGIES OF STUDENTS AT ENGLISH EDUCATION STUDY PROGRAM OF PATTIMURA UNIVERSITY AMBON; IMPLICATION FOR TEACHING LISTENING - Christian Albert Lewier; Priska Nendissa (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2020)
The present study investigated the implementation of various strategies performed by Indonesian EFL learners. Sixty students of English Education Study Program at Teachers Training and Educational Sciences Faculty of Pattimura University in Ambon were studied on their use of various listening strategies. The result of the study shows that most of these students applied social/affective strategies (76.6%) and metacognitive strategies (46.6%). The use of these strategies were favored by the students as listening strategy preferences due to their effectiveness in facilitating comprehension. The students’ perception on various strategies was identified and implication for teaching listening is further discussed in the article